STRIVING FOR SUCCESS TO BE A JOURNALIST IN DAVID FRANKEL'S THE DEVIL WEARS PRADA MOVIE (2006): AN INDIVIDUAL PSYCHOLOGICAL PERSPECTIVE - NUGRAHENI, TYAS (2011)
The object of the research is The Devil Wears Prada movie directed by David Frankel. The problem of the research is how striving for success to be a journalist is reflected in David Frankel's The Devil Wears Prada movie (2006): An Individual Psychological Perspective. The objectives of the research are to analyze the movie based on its structural elements and to analyze the movie based on individual psychological perspective. The study belongs to a qualitative study. In this research, the researcher uses two data sources namely primary and secondary data. The primary data source and object of study are the The Devil Wears Prada movie. Meanwhile the secondary ones are any literature relating with the study. The technique of data analysis in this study is descriptive method. Based on the analysis, the writer draws some conclusions as follows. First, based on structural analysis, it is clear that in this movie, the director delivers the message that people should focus and be consistent in order to reach their goal of life. The message of the movie delivered very clear by the structural elements of the movie. Second, based on psychological analysis, in this movie the director wants to give description about psychological condition of Andrea Sachs as the major character. The analysis shows how she strives to complete her sub goal in order to compensate her final goal to be a journalist. The analysis above includes some principles of individual psychology that is proposed by Alfred Adler. The principles are related with Andrea's personality, which is affected by her fictional final goal.